Study of the Use of Local Wisdom to Control Weeds to Support Sustainable Agricultural Businesses in Purworejo Village, Modayag District - Mokoginta, Agustinus; Pobela, Elva; Doa, Saskia (Universitas Pekalongan, 2024)
This research aims to determine the use of local wisdom to support sustainable agriculture. Research location in Purworejo and East Puwerejo Villages, Modayag District, East Bolaang Mongondow Regency. Data used in the form of primary data and secondary data. Primary data was obtained from farmers via a list of questions has been prepared, while secondary data is obtained from the District Office or Village Office. How to take samples using Purposive sampling with take as many samples as possible 20 farmer. The analysis used is descriptive analysis. Results This research shows that the farming community utilizes the local wisdom of weed plants before planting the weed plants, everything is cleaned, after that the weeds that have been cleaned are piled up with soil, their belief is that these weeds can produce natural fertilizer or nutrients for the plants to be planted.